Antonio Rosmini: His Life and Works - Swartz, Nico P (Advances in Social Sciences Research Journal, 2016)
Rosmini’s two works, Delle Cinque Piaghe Della Santa Chiesa and La Costituzione La Guistizia Sociale aroused great opposition especially among the Jesuits, and in 1849 these works were placed upon the Index. Rosmini’s philosophical writings embroiled him in theological controversies throughout his lifetime. The controversy around his philosophical works required more than one Papal injunction. But, seeing through neutral and an objective prism, Rosmini’s philosophy attempted to reconcile Catholic theology with modern political and social thought. In an audience with Pope Pius VII, Rosmini was encouraged by the latter to undertake the reform of philosophy. But Rosmini found himself wedged between the obligation to renew Catholic philosophy and finding his work on the Index. Before his death, Rosmini learned that the works in question were proclaimed free from censure by the Congregation of the Index.